Analisis Proses Hukum Atas Kasus Pelanggaran Kode Etik Anggota Kepolisian Yang Melakukan Tindak Pidana - Qaulan Sadidah (CV. ITTC INDONESIA, 2024)
The Indonesian National Police (Polri) is one of the governmental institutions responsible for enforcing the law in Indonesia. This task is not easy, as it is not only the community that must be aware of and comply with the law, but also the police themselves in determining which laws are more relevant and whether any violations align with existing legal provisions. The method employed in this research is qualitative. The findings of this study indicate that violations of the code of ethics committed by police officers who engage in criminal acts are processed through two legal channels: criminal prosecution and internal ethics hearings.